2019
DOI: 10.3390/su11195535
|View full text |Cite
|
Sign up to set email alerts
|

Customized Bus Network Design Based on Individual Reservation Demands

Abstract: With the advantages of congestion alleviation, environmental friendliness, as well as a better travel experience, the customized bus (CB) system to reduce individual motorized travel is highly popular in increasing numbers of cities in China. The line planning problem is a key aspect of the CB system. This paper presents a detailed flow chart of a CB network planning methodology, including individual reservation travel demand data processing, CB line origin–destination (OD) area division considering quantity c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“… Li et al (2019) analyzed the operational conditions of CB in Shanghai from the aspects of service level, in-vehicle time, travel time, and ticket price. Focusing on the people-bus-route matching problem, Han et al (2019) discovered the combination of 49-seat CB and 18-seat CB was the most economical of all options. Besides, CB with lower capacity tended to be more cost-effective than that with higher capacity.…”
Section: Literaturementioning
confidence: 99%
“… Li et al (2019) analyzed the operational conditions of CB in Shanghai from the aspects of service level, in-vehicle time, travel time, and ticket price. Focusing on the people-bus-route matching problem, Han et al (2019) discovered the combination of 49-seat CB and 18-seat CB was the most economical of all options. Besides, CB with lower capacity tended to be more cost-effective than that with higher capacity.…”
Section: Literaturementioning
confidence: 99%
“…Lyu et al [32] developed a framework called CB-Planner to jointly optimize stop locations, bus routing and timetables, and probabilistic mode choice, which maximized total profit. Han et al [33] presented an analytical model that minimized total cost and demonstrated that a mixed-size of bus fleet is cost-effective than a single-sized bus fleet. According to the findings discussed above, Table I summarizes the features of key studies focusing on the CB service.…”
Section: Customized Bus (Cb) Transitmentioning
confidence: 99%
“…That is because the vehicle with a larger capacity would pick up more passengers in a trip. However, according to Equation (6), the increase in occupancy increases the system's average service rate, which decreases the unit time of serving a passenger. Hence, passengers could make trip requests close to their desired time to decrease their travel costs.…”
Section: Effects Of Vehicle Occupancy/fleet Size Changesmentioning
confidence: 99%
“…Thanks to the advanced information and telecommunication technologies, travelers are allowed to take on-demand services or subscription bus services, especially in remote areas during peak hours [4,6]. An apparent trade-off is that transit users have to wait for the vehicle to pick them up and then stay in the vehicle, which may detour to pick up and drop off other users.…”
Section: Introductionmentioning
confidence: 99%